2021
DOI: 10.1016/j.ajem.2021.04.022
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic and governor mandated stay at home order on emergency department super utilizers

Abstract: Background Despite the trend of rising Emergency Department (ED) visits over the past decade, researchers have observed drastic declines in number of ED visits due to the COVID-19 pandemic. The purpose of the current study was to examine the impact of the COVID-19 pandemic and governor mandated Stay at Home Order on ED super utilizers. Methods This was a retrospective chart review of patients presenting to the 12 emergency departments of the Franciscan Mission of Our La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…In most of the studies available in the literature, there was a decrease in all priority codes, with the most accentuated reduction in the less urgent cases ( 2 , 3 , 5 , 13–17 ). Portugal’s approach resulted in a different pattern, as the epidemic was very well contained when it emerged.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the studies available in the literature, there was a decrease in all priority codes, with the most accentuated reduction in the less urgent cases ( 2 , 3 , 5 , 13–17 ). Portugal’s approach resulted in a different pattern, as the epidemic was very well contained when it emerged.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, other research has found that this age group is one of the largest populations who are without health insurance [ 33 ]. Other researchers found an increase in uninsured patients during COVID-19 [ 20 ], while another study found the rate of patients presenting with government insurance varied during the pandemic [ 34 ]. The cause for the decrease in the number of uninsured patients at our institution is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Those seeking help for mental health conditions seem to be the exception to these findings. Studies done early in the COVID-19 pandemic found that the demand for mental health services increased significantly [ 20 , 21 ] and especially for young adults [ 22 ]. Similar to emergency department s across the country, our large urban emergency department in New York City experienced a dramatic change in overall registrations during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies on ED revisits during the COVID-19 period. Although Alwood et al conducted a study on ED revisits during the COVID-19 period, it did not apply to the general public because it included only frequent ED users who visited the ED more than four times a year [13] . Therefore, we aim to identify ED revisit rates and characteristics of ED revisits in the COVID-19 period by comparing them with those in the pre-COVID-19 period.…”
Section: Introductionmentioning
confidence: 99%